U.S. College Tennis Athletes versus Australian International Scholarship Athletes - Marks, B. L.; Galleher, E. W.; Senga, M.; Katz, L. M. (2004)
The physiological demands of competitive tennis necessitate the training of both the anaerobic and aerobic energy systems for optimal tennis performance. Despite this knowledge, there is a surprising paucity of published information about the physical fitness and skill attributes of competitive tennis players at the U.S. college level. Therefore the purpose of this study was to determine how U.S. college tennis athletes compared to an international group of competitors. Twenty U.S. college tennis players (11 M, 9 F, 18-23 years old, average age = 19.5) were invited to participate in a series of evaluations. The U.S. athletes completed university-approved research participation consent forms. Published performance results from the AIS Tennis Program were used as the comparison group (n = 19; 7 males, 12 females; age: 16-19 years old). Two-tailed Student T-Tests were used to determine significant differences between the published AIS Tennis Program scores vs. the U.S. scores.